Front Cover: From 2D Graphene Nanosheets to 3D Graphene‐based Macrostructures (Chem. Asian J. 19/2020). Issue 19 (7th September 2020) - Mohd Firdaus, Rabita; Berrada, Nawal; Desforges, Alexandre; Mohamed, Abdul Rahman; Vigolo, Brigitte
Abstract : The assembly of nanomaterials such as graphene into 3D hierarchized macrostructures is definitely of great interest for a wide range of environmental applications. The main challenge of the present research remains to transfer the properties of a nanomaterial to a macroscopic material in a controlled manner so that the designed materials can have their own properties multiplied. More information can be found in the Minireview by Brigitte Vigolo, Abdul Rahman Mohamed et al.